Consumers Perceptions of the Ethics of Brand Placement in Hollywood Movies: A Cross-Cultural Study of Chinese and English Students at the University of Nottingham. - Fawcett, Oliver (2008)
This qualitative study explores how ethical brand placement in Hollywood movies is perceived to be by consumers. This industry has grown rapidly over the last few decades. However, the ethical guidelines in place are not currently sufficient to ensure the protection of the consumer. In an age of global advertising, promotional tools that offer a global reach are very important to advertising companies. If brand placement in movies is to be an effective global promotional tool it is necessary to understand how different cultures react to it. This study compares the views of Chinese and English students at the University of Nottingham. The findings suggest there is a difference between the views of the two cultures in their acceptability of brand placement. Several propositions for future research have been identified.